Increased Serum Phthalates (MEHP, DEHP) and Bisphenol A Concentrations in Children With Autism Spectrum Disorder: The Role of Endocrine Disruptors in Autism Etiopathogenesis. (April 2016) - Kardas, Fatih; Bayram, Ayse Kacar; Demirci, Esra; Akin, Leyla; Ozmen, Sevgi; Kendirci, Mustafa; Canpolat, Mehmet; Oztop, Didem Behice; Narin, Figen; Gumus, Hakan; Kumandas, Sefer; Per, Huseyin
The aim of this study was to investigate the relationship between autism spectrum disorders development and exposure to mono-(2-ethylhexyl)-phthalate (MEHP), di-(2-ethylhexyl)-phthalate (DEHP), and bisphenol A (BPA), 1 of the endocrine disruptors, among phthalates. The study included 48 children with autism spectrum disorder (27 boys, 21 girls) and 41 healthy subjects (24 boys, 17 girls) as controls. Serum MEHP, DEHP, and BPA levels were measured by using high-performance liquid chromatography. Children with autism spectrum disorder had significantly increased serum MEHP, DEHP, and BPA concentrations (0.47 ± 0.14 µg/ml, 2.70 ± 0.90 µg/ml, 1.25 ± 0.30 ng/ml) compared to healthy control subjects (0.29 ± 0.05 µg/ml, 1.62 ± 0.56 µg/ml, 0.88 ± 0.18 ng/ml) respectively ( P = .000). The fact that higher serum MEHP, DEHP, and BPA were found levels in the autism spectrum disorder group compared to healthy controls suggests that endocrine disruptors may have a role in the pathogenesis of autism spectrum disorders.